PENAMBANGAN BATUAN DI KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Siregar, Yusni Ikhwan (Jurnal Kajian Lingkungan, 2014)
This research aims to analyze 1) condition of rocks mining operations existing, 2) stakeholders understanding of good mining practice and 3) physical environment impact of rocks mining operations in sub district of Pangkalan Kerinci Regency of Pelalawan. The methods used to collect the data is a survey method with qualitative descriptive approach. The Mining operations existing condition of the eight mines do not have permit except locations III that only have mining permit (IUP). Mining system still uses an open system and not fully implement the K3 system, environmental protection and post-mining land cover. Stakeholders understanding about good mining practice include: aspects of licensing (72% = understand), technical mining (65% = understand), environmental protection (73% = understand), relationship of the upstream-downstream / conservation / value-added of community development / the area around the operation sites (66% = understand), frame rules regulations and applicable standards appropriate stages of mining operations (79% = very understand ). Health safety (44% = less understand), prepare a post-mining land ( 45% = less understand). Physical environmental impacts arising from mining, include: the loss of natural beauty, the loss of some habitat for flora and fauna, the increase in water runoff (surface run-off), noise (noise) and vibration (ground vibration) due to the operation of heavy equipment, air pollution, oil and used oil spills, soil subsidence and the presence of dry holes without plants.Keywords : Mining, Environmental Degradation, Pelalawan